Postprandial determination of Apo B-48 levels in whole plasma of healthy young individuals by a double-sandwich ELISA - Mantilla, Gerardo; Sierra, Iván D; Mendivil, Carlos O; Pérez, Clara E (MedUNAB, 2003)
Resumen High postprandial concentrrations of chylomicrons and its remnants are correlated with an atherosclerosis progression. Apolipoprotein B-48 is an essential component of these lipoproteins and appears to be a suitable marker for clinical studies of postprandial lipid metabolism and its relationship to cardiovascular risk. [Mantilla G, Sierra ID, Medivil CO, Péres CE. Postprandial determination of Apo B-48 levels in whole plasma of healthy young individuals by a double-sandwich ELISA. MedUNAB 2003; 6:130-6]. Key words: Apo B-48, postprandial lipemia, cardiovascular risk, immunoassay, chylomicrons, lipoproteins.